(untitled) (Emancipação, 2025)
This work seeks to study the interactions of the Borboletana group on WhatsApp among young people who suffer from eating disorders. The research seeks to verify how the construction of the ideal body happens, identify and describe the themes discussed and understand their submissions to the sacrifices of a troubled diet to achieve the ideal of the perfect body. The methodology comprises a study based on netnography (Kozinets, 2014). To this end, messages shared by the 39 participants were collected, from May 6th to May 21st, 2023. The analysis was divided into three categories: sociability in the group, the butterfly’s nest and the demonization of fat. Among the results, it is concluded that the community is constituted from the sense of belonging, social ties and shared interests. Furthermore, both interactions and media aspects contribute to the worsening of eating disorders.